2014
DOI: 10.1080/09613218.2014.979093
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the domestic building fabric performance gap

Abstract: In the UK, it is recognised that there is often a discrepancy between the measured fabric thermal performance of dwellings as-built and the predicted performance of the same dwellings and that the magnitude of this difference in performance can be quite large. This paper presents the results of a number of in-depth building fabric thermal performance tests that were undertaken on three case study dwellings located on two separate Passivhaus developments in the UK; one masonry cavity and the other two timber-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 6 publications
1
44
0
Order By: Relevance
“…These studies show another side of the performance gap: the buildings constructed following the Passivhaus standard [3] use to have no difference between the planned energy with the real energy consumption or even consume less energy. This fact is corroborated by other studies in the UK [4,5]. Therefore, it is possible to reduce the performance gap, designing and building in the right way.…”
Section: Introductionsupporting
confidence: 73%
“…These studies show another side of the performance gap: the buildings constructed following the Passivhaus standard [3] use to have no difference between the planned energy with the real energy consumption or even consume less energy. This fact is corroborated by other studies in the UK [4,5]. Therefore, it is possible to reduce the performance gap, designing and building in the right way.…”
Section: Introductionsupporting
confidence: 73%
“…The difference is often referred to as a "performance gap" and has been the subject of much research in recent times though some case studies [38] have found that in Passive House development the performance in-use is much closer to that predicted than for other types of new housing. Of course, the very low energy requirements associated with Passive House dwellings means there is an even greater expectation of high performance from occupants/clients and research has been conducted to examine these and their link to behavioural factors [39].…”
Section: Review Of Previous Researchmentioning
confidence: 99%
“…Unfortunately, there is a proven gap between the energy use predicted by models of buildings used to aid their design, or ensure compliance with national building codes, and the monitored energy consumption of the buildings once built. Many researchers claim that the measured energy consumption is frequently twice or more than that of the design stage prediction, [2][3][4] and although many studies have explored the performance gap from various perspectives, such as the role of poor workmanship or occupants' behaviour, the literacy of building energy modellers is rarely questioned. In addition, the literature indicates that in general, professionals (architects, engineers, sustainability experts, etc.)…”
Section: Introductionmentioning
confidence: 99%